Breeding for Salt-Resistance Using Transgressive Segregation in Spring Wheat (Journal of Sciences, Islamic Republic of Iran)
Hybrid populations (F3) derived from cross between four moderate salt-resistant spring wheat (Triticum aestivum L.) were assessed for transgressive segregation of salt-tolerant genotypes allowing germination and emergence at 350 mM NaCl for 30 days. The achieved Selection intensity was the order of 0.24-0.27 in these segregation populations (22-25 seedlings from 9000 seeds). Assessment of transgrassive individuals (more salt tolerant) and their parents was carried out in a hydroponics experiment applying six salt concentrations of 150, 200, 225, 250, 275 and 300 Mm NaCl. Root lengths of two-week-old seedlings grown in the different concentrations were used as salt-tolerant criteria. Root length of transgressive plants were longer than parents (except Tobari 66) showing more tolerance to NaCl. It may be assumed that the character in quantitative trait based, and the parents of such hybrids may contain different genes for salt tolerance.